TRANSFORMATION AND CHALLENGES OF PELUPELU INSTITUTION IN EKITILAND 1900-2000 (2015)
The colonial authorities created the pelupelu (kingship council) in 1900 for administrative purpose of Ekitiland. Existing studies on kingship traditions have focused largely on social and political developments during the colonial and post-colonial period, while the pelupelu, which embodies the people’s tradition and culture, has not attracted scholarly attention. This study, therefore investigated the pelupelu institution, it examined its transformation and challenges from 1900-2000. Historical research design, based on primary and secondary sources of data was adopted for the study. The primary sources included 32 key-informant interviews conducted with 24 kings, four high chiefs and four chief priests. Archival documents such as minutes of meetings, and colonial correspondence, including photographs were sourced from the National Archives in Ibadan. Secondary sources comprised newspapers, journal articles and books on kingship. Data were analysed using descriptive method of historical interpretations. Two types of kingship institution existed in Ekiti society by 1900 namely, elu (priest king) and the olu (crown head). Though, co-equal, and independent of each other, they were constituted as pelupelu by colonial authority in 1900. The taboo of seclusion prior to 1900 refrained the kings from attending pelupelu meeting. In 1913 the Native Authority Ordinance reversed the centralised administration and made the kings independent as president of the native authorities and courts in their respective administrative district. The introduction of tax in 1919 reduced the kings’ economic power but introduced salary based on revenue from their districts. Consequently, the kings were ready to federate and work for the colonial authorities, but the merger destroyed kingship culture and affected their traditional functions. Between 1920 and 1940, pelupelu was reconstituted to play civic roles. Problem of hierarchy and authority to wear crown became the order and dependent on colonial authority, which significantly disrupted the kings’ relationship. Ekiti Superior Native Authority proposed in 1940 fractured pelupelu rank but became functional from August 1944 as a miniature advisory council until 1952, when it was merged with the erroneously labelled Western House of Chiefs. In 1955, Ekiti society was re-organised into eight districts and the kings became unofficial members. From 1960 to 1975, the political elite subjected the kings to democratic principles and classified them in order of seniority; the 1976 Land Use Decree stripped them of their power over land. While their interaction has enabled them to have wider opinion on issues affecting Ekiti society, their structure into hierarchy during the colonial and classification in the post-colonial period created problem of competition, power politics, leadership struggle among the oba and between the traditional and the political elite. The selection of king is at the order of the state government against the tradition and culture of kingship. The colonial authorities took cognisance of cultural basis of development and involved the pelupelu institution in the administration of the Ekiti society. These endangered Ekiti kingship culture but facilitated social development. Government acknowledgement of the diversity of traditions and cultures as basis of development can further assist the government within the framework of national development.